THE SITUATION OF TRANSPORT INFRASTRUCTURE OF CITIES IN THE REPUBLIC OF KARAKALPAKISTAN - Gaypov, Sharipbay Djubatovich; Qunnazarova, Aynura Rametullaevna; Najenov , Dautbay Yakubbaevich (Educational Research in Universal Sciences, 2023)
This article is related to the planning of the transport system and the organization of public transport, taking into account the mobility of the population living in the remote areas of the Republic of Uzbekistan.